Assessing the resilience of adolescents who were raised in orphanages in Cairo, Egypt - Hassanin, Noha Emam (AUC Knowledge Fountain, 2019)
Orphans in Egypt face discrimination at school, in the work place and when finding a marriage partner. They also are at risk for developing physical, emotional and intellectual delays as a result of residing in an orphanage. The small amount of research conducted on orphans in Egypt has focused on these deficits and the hardships. However, it may be more empowering and more effective to focus on the strengths and capabilities of these youth. In particular, during adolescence when Egyptian orphans must leave their institutions, it is especially important to understand how to support resilience and give them the tools they need to handle the coming challenges of life, particularly in the context of the stigma they will face as they try to find a marriage partner, gain a job, and become independent. The current study assessed the resilience level of youth who resided in orphanages between the ages of 16 and 21, using the Arabic validated version of the CYRM-12 (The Child and Youth Resilience Measure). Those youth who scored the highest on this scale were then interviewed in order to investigate the factors that enabled their resilience. Forty-one youth were surveyed with a mean resilience score of 48.68, indicating high resilience. The youth who were interviewed emphasized the importance of having close supportive relationships especially with a caring adult, and they appreciated having access to material resources especially education. They also had a sense of cohesiveness inside their orphanages, along with a sense of social responsibility toward and social connection with their communities, their places of worship and other orphans. The interviewees were exposed to discrimination, but were able to navigate their way through this challenge using the support from the close relationships, their faith and religion, accepting who they were as orphans, and not caring about what others thought of them. They displayed high levels of self-efficacy and felt in control of their own situations and lives. These results showed how youth who reside in difficult conditions were able to successfully navigate their way to health sustaining resources within themselves, in the orphanage, and in their communities to enhance their well-being.